High CBX8 Expression Leads to Poor Prognosis in Laryngeal Squamous Cell Carcinoma by Inducing EMT by Activating the Wnt/β-Catenin Signaling Pathway - Meng, Qingchao; Li, Lei; Wang, Liping (Frontiers in Oncology, 2022)
Background: In this study, we detected the expression of chromobox protein homolog 8 (CBX8) in laryngeal squamous cell carcinoma (LSCC) and its influence on the occurrence and progression of LSCC. Methods: Pancancer analysis of CBX8 was analyzed by TCGA database and its expression in LSCC.The expression of CBX8 in 30 pairs of LSCC and adjacent tissues was analyzed by quantitative real-time PCR（qRT-PCR）and immunohistochemical assays, and its association with the prognosis and clinicopathological features of LSCC was further evaluated. A CBX8 knockdown model was constructed in AMC-HN-8 and Hep2 cell lines. The effects of CBX8 on LSCC cell proliferation, migration，invasion and apoptosis were detected by CCK8,EdU,wound healing, Transwell and flow cytometry assays. Levels of apoptosis-related protein，WNT/β-catenin signaling pathway and epithelial to mesenchymal transition (EMT) proteins, including Bax，Bcl2，β-catenin, DKK1, GSK3β, N-cadherin, E-cadherin and Snail1, in LSCC cells were detected by Western blotting. Results: CBX8 was overexpressed in LSCC. High expression of CBX8 in LSCC patients led to shorter overall survival and correlated with tumor stage and lymphatic metastasis. After CBX8 knockdown, the proliferation of AMC-HN-8 and Hep2 cells slowed, and the number of EdU-positive cells decreased. Wound healing slowed down, and the number of Transwell invading cells decreased. The percentage of apoptotic cells increased. The expression levels of Bcl2, β-catenin, N-cadherin and Snail11 proteins were significantly reduced in the CBX8 knockdown cells, while Bax, DKK1, GSK3β and E-cadherin significantly increased with their corresponding controls. Conclusion: CBX8 is highly expressed in LSCC and induces the EMT process by activating the Wnt/β-catenin signaling pathway to promote LSCC cell proliferation and migration and inhibit apoptosis, resulting in poor prognosis.